Military marriages: the aftermath of Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) deployments - Baptist, Joyce A.; Amanor-Boadu, Yvonne; Garrett, Kevin; Nelson Goff, Briana S.; Collum, Jonathan; Gamble, Paulicia; Gurss, Holly; Sanders-Hahs, Erin M.; Strader, Lizette; Wick, Stephanie (My University, 2012)
An examination of how members of military marriages were affected by and adapted to OIF/OEF deployment found three themes: communicating to stay connected, emotional and marital intimacy, and managing change. The findings demonstrate the nuanced and subtle nature of deployment-related challenges. While open and frequent communication was important in the adaptation process, communication was not synonymous with transparency. Unshared stories created a void that prevented couples from confiding in and supporting their partners. Although wives maintained their marriages by restraining sexual desires and over-extending their responsibilities post-deployment, these behaviors had a negative effect on marital quality. Clinical and research implications are discussed.
Keywords: Operation Iraqi Freedom; Operation Enduring Freedom; Qualitative study; Deployment stress; Military marriages